ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM PROVINSI NTT - Deshna Elisabeth Ledo; Alfred T. Rantelobo; J. Dessy Tapatfeto (JAKA - Jurnal Jurusan Akuntasi, 2021)
In Government Regulation No. 71/2010, the following four characteristics are the normative requirements needed so that government financial reports can meet the desired quality, namely: relevant, reliable, comparable, and understandable. The problems to be examined in this study are the factors that affect the quality of financial statement information.This study analyzes human resource competence, internal control systems, and technology utilization on the quality of financial report information at Kementerian Hukum Dan HAM Regional Office, NTT Province. This research includes quantitative research. Data collection was carried out by distributing questionnaires to employees of the Kemenkumham Regional Office's finance division. This study uses primary data, namely, research data obtained or collected directly from the original source. The statistical method used is multiple linear regression analysis techniques.This study's results are based on partial tests; human resource competence, technology use, and internal control systems have a positive effect on the quality of financial statement information. Moreover, based on the simultaneous test results, human resource competence, technology use, and internal control systems significantly affect the quality of financial report information at Kementerian Hukum Dan HAM Regional Office, NTT Province. This study concludes that the competence of human resources, technology use, and internal control systems affect the quality of financial report information at Kementerian Hukum Dan HAM Regional Office, NTT Province